Expert-oriented modelling of a 1vs1-situation in football - Leser, R.Moser, B.; Hoch, T.; Stögerer, J.; Kellermayr, G.; Reinsch, S.; Baca, A. (International Journal of Performance Analysis in Sport, 2015)
The aim of this study was to create a suitable model for analysing tactical behaviour in one versus one (1vs1) situations in association football. First, expert interviews were used to extract expert knowledge, in order to define an adequate kinematic testing model. Second, youth football players were examined via this model, and the data collected was used to check the suitability of the testing scheme. The performance of the players participating in 75 1vs1 trials was recorded via the LPM® (Local Positioning Measurement) system. In this context, another aim was to develop a concept to automate 1vs1 performance analysis.